2011
DOI: 10.1186/1756-3305-4-107
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance in malaria vector mosquitoes at four localities in Ghana, West Africa

Abstract: BackgroundMalaria vector control programmes that rely on insecticide-based interventions such as indoor house spraying with residual insecticides or insecticide treated bed nets, need to base their decision-making process on sound baseline data. More and more commercial entities in Africa, such as mining companies, are realising the value to staff productivity of controlling malaria transmission in their areas of operation.This paper presents baseline entomological data obtained during surveys conducted for fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 24 publications
(20 reference statements)
10
50
1
Order By: Relevance
“…Although DDT resistance is widely known in Ghana (25,26), resistance of this magnitude has not been described previously. Such highlevel resistance could render DDT ineffective for IRS-based vector-control programs and understanding the mechanisms underlying resistance is important for resistance management.…”
Section: Discussionmentioning
confidence: 99%
“…Although DDT resistance is widely known in Ghana (25,26), resistance of this magnitude has not been described previously. Such highlevel resistance could render DDT ineffective for IRS-based vector-control programs and understanding the mechanisms underlying resistance is important for resistance management.…”
Section: Discussionmentioning
confidence: 99%
“…Since data collection for the current study was done between October and November 2011, the observed distribution of sibling species of An. gambiae complex may vary periodically [41]. Significant variations in the relative frequencies of An.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence and rapid spread of Pyrethroid resistance in An. gambiae complex populations may be a threat for the sustainability of malaria vector control activities (Hunt et al, 2011;Temu et al, 2012). This raises the need for national surveys for monitoring the insecticide susceptibility status of major vectors, detection of resistance possible genes and assessing their implications on vector control activities (Kelly-Hope & Ranson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In many African countries, Anopheline mosquitoes are developing resistance to all classes of insecticides used for mosquito control (Hunt et al, 2011;Kabula et al, 2012). Among these, Pyrethroids are the only option for net treatment due to their relative safety for humans at low dosage, excito-repellent properties, rapid rate of knock-down, and killing effects (Zaim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%